The DETERMINANTS OF AUDIT QUALITY AT PUBLIC ACCOUNTANT FIRMS IN SEMARANG CITY - Yuniarsih, Nia (JEA17: Jurnal Ekonomi Akuntansi, 2023)
Audit quality is still widely questioned by the public because there are still various public assessments in assessing public accountant firms, this assessment can be measured by the competence of auditors who are evaluated in the audit process. Apart from problems related to auditor competence, the same is the case with auditor integrity and ethics, which are factors that determine the audit quality of a public accountant firm. This study aimed to determine the effect of independence, auditor ethics and work experience on audit quality. This study uses quantitative methods with primary data obtained from distributing questionnaires. The population in this study were all senior auditors and junior auditors at KAP in Semarang with the Convenience Sampling technique. Researchers managed to collect 30 respondents. Data analysis was performed using multiple linear regression. Based on this study, the variables of independence, auditor ethics and work experience affect audit quality.